The Comparison of Antibacterial Activity Between Cresophene and Garlic on Isolated of Bacteria in The Necrotic Deciduous Tooth - Nurliana, -; Bramanti, I; Sudarso, ISR; Wahyunigsih, MSH; Wibawa, T (International Journal of Human and Health Sciences (IJHHS), 2020)
Background : This study aims to compare the ability of two medicaments between cresophene and garlic on antibacterial activity of isolate deciduous necrotic teeth. Methods: In vitro test to see the antibacterial activity was carried out on the aerobic and anaerobic bacteria taken straight from the necrotic tooth of pediatric patients (aged 4-7 years old) that treated for endodontics in Pediatric Dental Clinic of RSGMUGM Prof Soedomo. Bacterial identification using the CLSI Standardized Method 2012 and Biochemical identification by Thermo Scientific Rapid System 2010 guideline. In this identification, was founded three species: Prevotella bivia, Serratia marcescens and Clostridium innocum. This test was carried out quantitative measurements to see the inhibition zone of bacterial growth. Whether cresophene has antibacterial potential test results from using an analytical descriptive test that was tabulated.Study group treated with cresophene in a well of 0.7 cm at a dose of 75 μL, garlic extract at a dose of 75 μL divided into five groups with concentrations of 20%, 40%, 60%, 80%, and garlic filtrate. Comparison of the cresophene and garlic effect conducted in vitro by looking at the inhibition zone of the bacterial growth. Results: In all groups, there are inhibitory zones. Cresophene against bacteria Prevotella bivia (54mm), Clostridium innocum (30 mm), Clostridium perfringens (26 mm), Serratia macescens (26 mm), S.mutans (54 mm), while garlic extract against bacteria Prevotella bivia, Clostridium innocum, Clostridium perfringens, S.mutansdonot show againt inhibitory, Serratia macescens (10mm, in concentration of 80 %) and garlic filtrate against bacteria Prevotella bivia (51 mm), Clostridium innocum (28 mm), Clostridium perfringens (46 mm), Serratia marcescens (31 mm), S.mutans (49 mm). Conclusion: Cresophene has a greater inhibition than garlic extract, but it is lower than garlic filtrate. International Journal of Human and Health Sciences Vol. 04 No. 04 October’20 Page : 287-290